There is no best surgical treatment for chronic isolated syndesmotic instability: a systematic review. Issue 5 (12th August 2016) - Lubberts, Bart; van Dijk, Pim A D; Calder, James D; DiGiovanni, Christopher W
Abstract : Importance: Appropriate management of chronic isolated ankle syndesmotic injuries is needed to prevent the development of concomitant pathology. Previous studies have evaluated treatment and outcomes of chronic syndesmotic injuries. However, these studies did not distinguish between isolated—an injury without associated fibula fracture—and non-isolated syndesmotic injuries. Objective: We conducted a systematic review to assess the functional outcomes and determine evidence for optimal management of chronic isolated syndesmotic injuries. Evidence review: A review of the literature was performed according to the PRISMA guidelines. PubMed, EMBASE and the Cochrane Library were searched on 2 May 2016. Studies were identified by using synonyms for 'ankle syndesmosis', 'injury', 'delayed', 'chronic' and 'treatment'. Findings: The search resulted in 216 reports on PubMed, 86 on EMBASE and 3 on the Cochrane Library. After reading the remaining full-text articles, we included 11 studies describing outcomes after surgical management of chronic unstable isolated injuries. Conclusions and relevance: Currently, there is no evidence to support or refute any of the surgical interventions performed for chronic unstable isolated syndesmotic injuries. High level of evidence research is warranted if we want to establish optimal treatment.